me4soc: a multi-model ensemble interface for soil organic carbon predictions - Elisa Bruni; Aleksi Lehtonen; Shoji Hashimoto; Boris Ťupek; Nasser Bacha; Daniel Bunker; Illian Brasselet-Darracq; Dalia Fages-Gouyou; Yanis Hemeray; Christopher P.O. Reyer; Carlos A. Sierra; Bertrand Guenet (Ecological Modelling, 2026)

Genetic selection for resistance to Francisella orientalis shows significant selection response in Nile tilapia - Baltasar F. Garcia; Jairo A. Restrepo-Arango; Marcelo S. Silva Filho; Elielma L. Sousa; John F.G. Agudelo; Vito A. Mastrochirico-Filho; Shisley C.S. Manso; Carolina S. Pereira; Danielle C. Dias; Antonio F.G. Leonardo; Fernando S. Fonseca; Leonardo Tachibana; et al. (Aquaculture, 2025)

Genomic predictions for resistance to Aeromonas hydrophila in pacu (Piaractus mesopotamicus) - Shisley C.S. Manso; Baltasar F. Garcia; Vito A. Mastrochirico-Filho; Fábio Porto-Foresti; José M. Yáñez; Diogo T. Hashimoto (Aquaculture, 2024)

Genetic parameters for host-response to acanthocephaliasis caused by the endoparasite Neoechinorhynchus buttnerae in the Amazon fish Colossoma macropomum - John F.G. Agudelo; Baltasar F.G. Neto; Vito A. Mastrochirico-Filho; Raquel B. Ariede; Luis F.S. Moreira; Leilane da Silva Noronha; José M. Yáñez; Alexandre Honczaryk; Gustavo M.R. Valladão; Diogo T. Hashimoto (Aquaculture, 2024)

Geographic Drivers of Genetic and Plumage Color Diversity in the Blue-Crowned Manakin - Pedro Paulo; Fernando Henrique Teófilo; Carolina Bertuol; Érico Polo; Andre E. Moncrieff; Lucas N. Bandeira; Claudia Nuñez-Penichet; Igor Yuri Fernandes; Mariane Bosholn; Arielli F. Machado; Leilton Willians Luna; Willian Thomaz Peçanha; et al. (Evolutionary Biology, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Navigating ecological security research over the last 30 years: a scoping review - Benhui Zhu; Shizuka Hashimoto; Samuel A. Cushman (Sustainability Science, 2023)
Intensification of human activities is pushing our use of ecosystems beyond thresholds of resiliency. Given the accelerating global crisis of ecological sustainability, there has been enormous growth in research related to ecological security. However, differences in opinions on ecological security have hindered understanding and effective applications of this concept. To understand the development of research on ecological security, we reviewed its achievements and limitations over the past 30 years from three dimensions: definition, evaluation method, and approach to identify measures to improve the ecological security level. We used the Web of Science search engine to retrieve peer-reviewed journal articles published from 1990 to 2021 containing the keywords “ecological security” or “ecological safety”. There are three main ethical perspectives among the definitions of ecological security: nature-centric, human-centric, and eclectic; the human-centric view, which focuses on human well-being, is predominant in the field. Most studies employed the following three evaluation methods: quantitative comparison, composite indicators, and spatial analysis. However, the results of ecological security analyses were difficult to compare. Three main approaches (causality, correlation, and landscape) were used to identify the drivers of ecological security and propose measures for ensuring or improving ecological security. Owing to the complexity and heterogeneity of ecosystems, universally effective measures to ensure ecological security rarely exist. For the definition and evaluation of ecological security, a broader, non-anthropocentric perspective that incorporates the intrinsic value of non-humans in the context of cost–benefit, security–efficiency evaluations is essential. When proposing evaluation methods, the comparability of evaluation results should be given priority. To improve ecological security level, identifying the key drivers and/or potential optimal patterns of ecological security may be a promising solution.

A two concentric circles model incorporating availability of ecosystem services and affordability of humans to clarify the ecological security concept - Benhui Zhu; Shizuka Hashimoto; Samuel A Cushman (Ecological Modelling, 2023)

Bringing the Nature Futures Framework to life: creating a set of illustrative narratives of nature futures - América Paz Durán; Jan J. Kuiper; Ana Paula Dutra Aguiar; William W. L. Cheung; Mariteuw Chimère Diaw; Ghassen Halouani; Shizuka Hashimoto; Maria A. Gasalla; Garry D. Peterson; Machteld A. Schoolenberg; Rovshan Abbasov; Lilibeth A. Acosta; et al. (Sustainability Science, 2023)
To halt further destruction of the biosphere, most people and societies around the globe need to transform their relationships with nature. The internationally agreed vision under the Convention of Biological Diversity—Living in harmony with nature—is that “By 2050, biodiversity is valued, conserved, restored and wisely used, maintaining ecosystem services, sustaining a healthy planet and delivering benefits essential for all people”. In this context, there are a variety of debates between alternative perspectives on how to achieve this vision. Yet, scenarios and models that are able to explore these debates in the context of “living in harmony with nature” have not been widely developed. To address this gap, the Nature Futures Framework has been developed to catalyse the development of new scenarios and models that embrace a plurality of perspectives on desirable futures for nature and people. In this paper, members of the IPBES task force on scenarios and models provide an example of how the Nature Futures Framework can be implemented for the development of illustrative narratives representing a diversity of desirable nature futures: information that can be used to assess and develop scenarios and models whilst acknowledging the underpinning value perspectives on nature. Here, the term illustrative reflects the multiple ways in which desired nature futures can be captured by these narratives. In addition, to explore the interdependence between narratives, and therefore their potential to be translated into scenarios and models, the six narratives developed here were assessed around three areas of the transformative change debate, specifically, (1) land sparing vs. land sharing, (2) Half Earth vs. Whole Earth conservation, and (3) green growth vs. post-growth economic development. The paper concludes with an assessment of how the Nature Futures Framework could be used to assist in developing and articulating transformative pathways towards desirable nature futures.

High-throughput phenotyping by deep learning to include body shape in the breeding program of pacu (Piaractus mesopotamicus) - Milena V. Freitas; Celma G. Lemos; Raquel B. Ariede; John F.G. Agudelo; Rubens R.O. Neto; Carolina H.S. Borges; Vito A. Mastrochirico-Filho; Fábio Porto-Foresti; Rogério L. Iope; Fabrício M. Batista; José R.F. Brega; Diogo T. Hashimoto (Aquaculture, 2023)

Genome-wide association study of host resistance to the ectoparasite Ichthyophthirius multifiliis in the Amazon fish Colossoma macropomum - Lieschen V. G. Lira; Vito A. Mastrochirico-Filho; Natalia J. Mendes; Raquel B. Ariede; José M. Yáñez; Diogo T. Hashimoto (Molecular Biology Reports, 2023)

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Altered Notch Signaling in Developing Molar Teeth of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Deficient Mice - B. D. Fulop; B. Sandor; E. Szentleleky; E. Karanyicz; D. Reglodi; B. Gaszner; R. Zakany; H. Hashimoto; T. Juhasz; A. Tamas (Journal of Molecular Neuroscience, 2019)

Correction to: Ceramicines M–P from Chisocheton ceramicus: isolation and structure–activity relationship study - Alfarius Eko Nugroho; Akiyo Hashimoto; Chin-Piow Wong; Hiromasa Yokoe; Masayoshi Tsubuki; Toshio Kaneda; A. Hamid A. Hadi; Hiroshi Morita (Journal of Natural Medicines, 2019)
The article Ceramicines M–P from Chisocheton ceramicus : isolation and structure–activity relationship study.

Mitochondrial orf463 causing male sterility in radish is possessed by cultivars belonging to the ‘Niger’ group - H. Yamagishi; Y. Tanaka; S. Shiiba; A. Hashimoto; A. Fukunaga; T. Terachi (Euphytica, 2019)

Novel Defense by Metallothionein Induction Against Cognitive Decline: From Amyloid β1–42-Induced Excess Zn2+ to Functional Zn2+ Deficiency - Atsushi Takeda; Haruna Tamano; Wakana Hashimoto; Shuhei Kobuchi; Hiroki Suzuki; Taku Murakami; Munekazu Tempaku; Yuta Koike; Paul A. Adlard; Ashley I. Bush (Molecular Neurobiology, 2018)

Greener approaches to the measurement of polyaromatic hydrocarbons (PAHs) in unused and used crankcase motor oils from Malaysia - Kannan Narayanan; Haruhiko Miyagawa; Riki Kitano; Katsuhiro Nakagawa; Megumi Hirooka; Shunji Hashimoto; Vladimir P. Beskoski; Haris Hafizal Abd Hamida; Fatemeh A. Jahromi; Ignatius Phang; Ahmad Zaharin Aris; Donghao Li; et al. (Environmental Science and Pollution Research, 2018)

Development of microsatellite markers using next-generation sequencing for the fish Colossoma macropomum - Raquel B. Ariede; Milena V. Freitas; Milene E. Hata; Vito A. Matrochirico-Filho; Ricardo Utsunomia; Fernando F. Mendonça; Fausto Foresti; Fábio Porto-Foresti; Diogo T. Hashimoto (Molecular Biology Reports, 2018)

Ceramicines M–P from Chisocheton ceramicus: isolation and structure–activity relationship study - Alfarius Eko Nugroho; Akiyo Hashimoto; Chin-Piow Wong; Hiromasa Yokoe; Masayoshi Tsubuki; Toshio Kaneda; A. Hamid A. Hadi; Hiroshi Morita (Journal of Natural Medicines, 2018)
Ceramicines are a series of limonoids which were isolated from the bark of Malaysian Chisocheton ceramicus (Meliaceae) and show various biological activities. Ceramicine B, in particular, has been reported to show a strong lipid droplet accumulation (LDA) inhibitory activity on a mouse pre-adipocyte cell line (MC3T3-G2/PA6). With the purpose of discovering compounds with stronger activity than ceramicine B, we further investigated the constituents of C. ceramicus . As a result, from the bark of C. ceramicus four new ceramicines (ceramicines M–P, 1 – 4 ) were isolated, and their structures were determined on the basis of NMR and mass spectroscopic analyses in combination with NMR chemical shift calculations. LDA inhibitory activity of 1 – 4 was evaluated. Compounds 1 – 3 showed LDA inhibitory activity, and 3 showed better selectivity than ceramicine B while showing activity at the same order of magnitude as ceramicine B. Since 3 , which possess a carbonyl group at C-7, showed better selectivity than 5 , which possess a 7α-OH group, while showing activity at the same order of magnitude as 5 , we also investigated the effect of the substituent at C-7 by synthesizing several derivatives and evaluating their LDA inhibitory activity. Accordingly, we confirmed the importance of the presence of a 7α-OH group to the LDA inhibitory activity.

Clinical significance of Aspergillus species isolated from respiratory specimens in patients with Mycobacterium avium complex lung disease - K. Furuuchi; A. Ito; T. Hashimoto; S. Kumagai; T. Ishida (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Origin of B chromosomes in the genus Astyanax (Characiformes, Characidae) and the limits of chromosome painting - Duílio M. Z. de A. Silva; Sandro Natal Daniel; Juan Pedro M. Camacho; Ricardo Utsunomia; Francisco J. Ruiz-Ruano; Manolo Penitente; José Carlos Pansonato-Alves; Diogo Teruo Hashimoto; Claudio Oliveira; Fábio Porto-Foresti; Fausto Foresti (Molecular Genetics and Genomics, 2016)

Structural and Morphometric Comparison of Lower Incisors in PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; D. Reglodi; D. B. Fulop; Z. Helyes; I. Szanto; P. Nagy; H. Hashimoto; A. Tamas (Journal of Molecular Neuroscience, 2016)

Triassic–Jurassic granites on the Lord Howe Rise, northern Zealandia - N. Mortimer; R. E. Turnbull; J. M. Palin; A. J. Tulloch; N. Rollet; T. Hashimoto (Australian Journal of Earth Sciences, 2015)

Impact of bacterial coinfection on clinical outcomes in pneumococcal pneumonia - S. Kumagai; T. Ishida; H. Tachibana; Y. Ito; A. Ito; T. Hashimoto (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Reductions in synaptic proteins and selective alteration of prepulse inhibition in male C57BL/6 mice after postnatal administration of a VIP receptor (VIPR2) agonist - Yukio Ago; Michael C. Condro; Yossan-Var Tan; Cristina A. Ghiani; Christopher S. Colwell; Jesse D. Cushman; Michael S. Fanselow; Hitoshi Hashimoto; James A. Waschek (Psychopharmacology, 2015)

Structural and Morphometric Comparison of the Molar Teeth in Pre-eruptive Developmental Stage of PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; Sz. Felszeghy; T. Juhasz; D. Reglodi; L. Mark; P. Kiss; A. Jungling; B. D. Fulop; A. D. Nagy; H. Hashimoto; R. Zakany; et al. (Journal of Molecular Neuroscience, 2014)

Comparative Protein Composition of the Brains of PACAP-Deficient Mice Using Mass Spectrometry-Based Proteomic Analysis - G. Maasz; Z. Pirger; D. Reglodi; D. Petrovics; J. Schmidt; P. Kiss; A. Rivnyak; H. Hashimoto; P. Avar; E. Jambor; A. Tamas; B. Gaszner; et al. (Journal of Molecular Neuroscience, 2014)

Association between perceived inadequate staffing and musculoskeletal pain among hospital patient care workers - Seung-Sup Kim; Cassandra A. Okechukwu; Jack T. Dennerlein; Leslie I. Boden; Karen Hopcia; Dean M. Hashimoto; Glorian Sorensen (International Archives of Occupational and Environmental Health, 2014)

Examination of Calcium-Binding Protein Expression in the Inner Ear of Wild-Type, Heterozygous and Homozygous Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Knockout Mice in Kanamycin-Induced Ototoxicity - A. Nemeth; K. Szabadfi; B. Fulop; D. Reglodi; P. Kiss; J. Farkas; B. Szalontai; R. Gabriel; H. Hashimoto; A. Tamas (Neurotoxicity Research, 2014)

Chromosomal organization of repetitive DNA sequences in Astyanax bockmanni (Teleostei, Characiformes): dispersive location, association and co-localization in the genome - Duílio M. Z. A. Silva; José Carlos Pansonato-Alves; Ricardo Utsunomia; Sandro Natal Daniel; Diogo Teruo Hashimoto; Claudio Oliveira; Fabio Porto-Foresti; Fausto Foresti (Genetica, 2013)

A large hydrothermal reservoir beneath Taal Volcano (Philippines) revealed by magnetotelluric resistivity survey: 2D resistivity modeling - Y. Yamaya; P. K. B. Alanis; A. Takeuchi; J. M. Cordon; T. Mogi; T. Hashimoto; Y. Sasai; T. Nagao (Bulletin of Volcanology, 2013)

Exceptionally high conservation of the MHC class I-related gene, MR1, among mammals - Kentaro Tsukamoto; Janine E. Deakin; Jennifer A. Marshall Graves; Keiichiro Hashimoto (Immunogenetics, 2013)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice - D. Reglodi; P. Kiss; K. Szabadfi; T. Atlasz; R. Gabriel; G. Horvath; P. Szakaly; B. Sandor; A. Lubics; E. Laszlo; J. Farkas; A. Matkovits; et al. (Journal of Molecular Neuroscience, 2012)

Development and characterization of microsatellite loci in Phractocephalus hemioliopterus (Siluriformes: Pimelodidae) and their cross-species amplification in six related species - C. A. Souza; D. T. Hashimoto; L. H. G. Pereira; C. Oliveira; F. Foresti; F. Porto-Foresti (Conservation Genetics Resources, 2012)

Interspecific fish hybrids in Brazil: management of genetic resources for sustainable use - Diogo T. Hashimoto; José A. Senhorini; Fausto Foresti; Fábio Porto‐Foresti (Reviews in Aquaculture, 2012)
Serrasalmid and pimelodid fish hybrids represent important advances for aquaculture in Brazil, but they also constitute serious genetic risks to cultivated and natural populations. Serrasalmid hybrids (‘tambacu’, ‘tambatinga’ and ‘patinga’) result from crosses between Colossoma macropomum , Piaractus mesopotamicus and Piaractus brachypomus . Pimelodid hybrids (‘ponto e vírgula’, ‘cachandiá’ and ‘cachapira’) arise from crosses between Pseudoplatystoma corruscans , Pseudoplatystoma reticulatum , Phractocephalus hemioliopterus and Leiarius marmoratus . The problems associated with hybrids mainly result from inappropriate use because these animals are reproductively compatible with their parental species. This review shows that monitoring of fish hybrids using genetic techniques is necessary for their sustainable development in aquaculture. The genetic technologies used to identify fish hybrids include cytogenetic methods, which are considered to be low cost, and polymerase chain reaction‐based molecular markers, which are associated with high throughput. Therefore, both types of genetic methodologies should be applied in monitoring programs aimed at brood stock management, wild stocks, the trade of hybrid juveniles and processed fish products in markets. Moreover, physical and genetic confinement of hybrids in aquaculture operations will be necessary to avoid the problems posed by these animals. The expected result of these measures will be the production of genetically improved animals by fish farms, allowing the sector to develop further and offering high‐quality animal protein.

Comparative Examination of Inner Ear in Wild Type and Pituitary Adenylate Cyclase Activating Polypeptide (PACAP)-Deficient Mice - A. Tamas; K. Szabadfi; A. Nemeth; B. Fulop; P. Kiss; T. Atlasz; R. Gabriel; H. Hashimoto; A. Baba; N. Shintani; Zs. Helyes; D. Reglodi (Neurotoxicity Research, 2012)

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo - K. Szabadfi; T. Atlasz; P. Kiss; B. Danyadi; A. Tamas; Zs. Helyes; H. Hashimoto; N. Shintani; A. Baba; G. Toth; R. Gabriel; D. Reglodi (Neurotoxicity Research, 2012)

Antifouling properties of tough gels against barnacles in a long-term marine environment experiment - T. Murosaki; T. Noguchi; K. Hashimoto; A. Kakugo; T. Kurokawa; J. Saito; Y. M. Chen; H. Furukawa; J. P. Gong (Biofouling, 2009)

Cell and receptor type-specific alterations in markers of GABA neurotransmission in the prefrontal cortex of subjects with schizophrenia - David A. Lewis; Takanori Hashimoto; Harvey M. Morris (Neurotoxicity Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Constraining rooting depths in tropical rainforests using satellite data and ecosystem modeling for accurate simulation of gross primary production seasonality - KAZUHITO ICHII; HIROFUMI HASHIMOTO; MICHAEL A. WHITE; CHRISTOPHER POTTER; LUCY R. HUTYRA; ALFREDO R. HUETE; RANGA B. MYNENI; RAMAKRISHNA R. NEMANI (Global Change Biology, 2007)
Accurate parameterization of rooting depth is difficult but important for capturing the spatio‐temporal dynamics of carbon, water and energy cycles in tropical forests. In this study, we adopted a new approach to constrain rooting depth in terrestrial ecosystem models over the Amazon using satellite data [moderate resolution imaging spectroradiometer (MODIS) enhanced vegetation index (EVI)] and Biome‐BGC terrestrial ecosystem model. We simulated seasonal variations in gross primary production (GPP) using different rooting depths (1, 3, 5, and 10 m) at point and spatial scales to investigate how rooting depth affects modeled seasonal GPP variations and to determine which rooting depth simulates GPP consistent with satellite‐based observations. First, we confirmed that rooting depth strongly controls modeled GPP seasonal variations and that only deep rooting systems can successfully track flux‐based GPP seasonality at the Tapajos km67 flux site. Second, spatial analysis showed that the model can reproduce the seasonal variations in satellite‐based EVI seasonality, however, with required rooting depths strongly dependent on precipitation and the dry season length. For example, a shallow rooting depth (1–3 m) is sufficient in regions with a short dry season (e.g. 0–2 months), and deeper roots are required in regions with a longer dry season (e.g. 3–5 and 5–10 m for the regions with 3–4 and 5–6 months dry season, respectively). Our analysis suggests that setting of proper rooting depths is important to simulating GPP seasonality in tropical forests, and the use of satellite data can help to constrain the spatial variability of rooting depth.

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

High frequency Agrobacterium-mediated transformation and plant regeneration via direct shoot formation from leaf explants in Beta vulgaris and Beta maritima - H. Hisano; Y. Kimoto; H. Hayakawa; J. Takeichi; T. Domae; R. Hashimoto; J. Abe; S. Asano; A. Kanazawa; Y. Shimamoto (Plant Cell Reports, 2004)

Phylogenetic relationships of deep-sea mussels of the genus Bathymodiolus (Bivalvia: Mytilidae) - J.-I. Miyazaki; M. Shintaku; A. Kyuno; Y. Fujiwara; J. Hashimoto; H. Iwasaki (Marine Biology, 2004)

In situ pressure–temperature conditions of a tectonic mélange: Constraints from fluid inclusion analysis of syn‐mélange veins - Y. Hashimoto; M. Enjoji; A. Sakaguchi; G. Kimura (Island Arc, 2003)
Pressure and temperature (P–T) conditions of mélange formation are estimated from fluid inclusions within “syn‐mélange” veins developed in the necks of boudins of sandstone blocks in the mélange of the Shimanto accretionary complex, south‐west Japan. The mélange records décollement‐zone processes. P–T conditions are in the range of 81 (+15) to 235 (±18) MPa and 150 (±25) to 220 (±31)°C. Assuming a constant fluid‐pressure to lithostatic‐pressure ratio for each data set, we estimate a P–T gradient of between 10.0°C/km (+0.2/−1.5) (lithostatic pressure) and 4.2°C/km (+0.1/−0.9) (hydrostatic pressure) from these results. The estimated lithostatic P–T gradient is much lower than that calculated from the age of the subducting oceanic plate. The estimated P–T conditions suggest that the mélange was formed within the seismogenic zone (hypothesized from thermal modeling), although the deformation mechanism of mélange (i.e. dominant diffusive mass transfer mainly in shale matrix with minor brittle breakage mainly in sandstone blocks) does not show evidence of seismic deformation. In addition, at the time of syn‐mélange vein formation, a shale matrix of mélange has injected into the vein, which indicates a ductile deformation of shale. A possible explanation for this discrepancy is that the mélange was formed during the interseismic period.

How fruit abundance affects the chimpanzee party size: a comparison between four study sites - Chie Hashimoto; Shigeru Suzuki; Yuji Takenoshita; Juichi Yamagiwa; A. Kanyunyi Basabose; Takeshi Furuichi (Primates, 2003)

3. Histaminergic mechanisms in the brain¶Possible involvement of the chorda tympani nerve in stimulation of the histaminergic system by leptin - T. Morimoto-Ishizuka; Y. Treesukosol; Y. Yamamoto; K. Yamamoto; T. Hashimoto; A. Yamatodani (Inflammation Research, 2002)

Retrolyc1 subfamilies defined by different U3 LTR regulatory regions in the Lycopersicon genus - P. Araujo; J. Casacuberta; A. Costa; R. Hashimoto; M.-A. Grandbastien; M.-A. Van Sluys (Molecular Genetics and Genomics, 2001)

A method for detecting myocardial abnormality by using a total current-vector calculated from ST-segment deviation of a magnetocardiogram signal - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

A method for detecting myocardial abnormality by using a current-ratio map calculated from an exercise-induced magnetocardiogram - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

Structure of the infected cell protein 0 gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 2000)

In vitro characterization of J-113397, a non-peptide nociceptin/orphanin FQ receptor antagonist - R. Bigoni; G. Calo'; A. Rizzi; R. Guerrini; C. De Risi; Y. Hashimoto; E. Hashiba; D.G. Lambert; D. Regoli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Antibacterial characteristics of magnesium oxide powder - J. Sawai; H. Kojima; H. Igarashi; A. Hashimoto; S. Shoji; T. Sawaki; A. Hakoda; E. Kawada; T. Kokugan; M. Shimizu (World Journal of Microbiology and Biotechnology, 2000)

A major metabolite of aceclofenac, 4′-hydroxy aceclofenac, suppresses the production of interstitial pro-collagenase/proMMP-1 and pro-stromelysin-1/proMMP-3 by human rheumatoid synovial cells - R. Yamazaki; S. Kawai; Y. Mizushima; T. Matsuzaki; S. Hashimoto; T. Yokokura; A. Ito (Inflammation Research, 2000)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Glycogen storage disease III subtypes and muscle weakness during childhood - M. Okubo; A. Horinishi; M. Hashimoto; H. Kanno; T. Murase (Human Genetics, 1999)

Structure of the immediate early gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 1999)

Mixture in the distribution of haloperidol-induced oral dyskinesias in the rat supports an animal model of tardive dyskinesia - Takeshi Hashimoto; David E. Ross; Xue-Min Gao; Deborah R. Medoff; C. A. Tamminga (Psychopharmacology, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

RT1.P , rat class Ib genes related to mouse TL : evidence that CD1 molecules but not authentic TL antigens are expressed by rat thymus - A. Matsuura; Shinichi Takayama; Miyuki Kinebuchi; Yuji Hashimoto; Kiyoshi Kasai; Daisuke Kozutsumi; Shingo Ichimiya; Ryoichi Honda; Takashi Natori; Kokichi Kikuchi (Immunogenetics, 1997)

Methane-oxidizing activities and methanotrophic populations associated with wetland rice plants - I. Watanabe; T. Hashimoto; A. Shimoyama (Biology and Fertility of Soils, 1997)

Preparation of Japanese encephalitis virus nonstructural protein NS1 obtained from culture fluid of JEV-infected Vero cells - T. Lee; K. Watanabe; C. Aizawa; A. Nomoto; H. Hashimoto (Archives of Virology, 1991)

Evidence for the presence of a genome-linked protein in infectious flacherie virus - Y. Hashimoto; A. Watanabe; S. Kawase (Archives of Virology, 1986)

Ultrastructural changes of motoneurons in monkeys infected with enterovirus 71 - I. Hashimoto; A. Hagiwara; I. Uchino (Archives of Virology, 1985)

Genetic and phenotypic characteristics of enterovirus 71 isolates from patients with encephalitis and with hand, foot and mouth disease - A. Hagiwara; T. Yoneyama; S. Takami; I. Hashimoto (Archives of Virology, 1984)

Neurovirulence in cynomolgus monkeys of enterovirus 71 isolated from a patient with hand, foot and mouth disease - I. Hashimoto; A. Hagiwara; H. Kodama (Archives of Virology, 1978)